Análise de sensibilidade na metodologia nodal para o cálculo da tarifa de uso do sistema de transmissão - Lucchese, Felipe Cirolini (2018)
The reform of the 90s resulted in a vast impact on the Brazilian electrical system, mainly due to privatizations that occurred in that decade. The opening in the energy market has de-verticalized the four sectors of the area: generation, transmission, distribution and commercialization. However, transmission and distribution have a natural monopoly effect so their service is granted and regulated by the electric energy national agency (ANEEL). The Brazilian transmission system is one of the largest in the world due to a concentration of consumers in the coastal region while most of the sources are in the interior of the country. The construction and maintenance of theses facility’s requires a large investment of capital and needs to be provided by a guaranteed remuneration for its service. As a result, the state regulation has stablish a tax for the grid users called, Tariff for Use of the Transmission System (TUST), in order to recover costs with the transmission system. In order to form a price, Brazil adopted the Nodal methodology, to determine the rates charged for energy transportation. This methodology characteristic provides the complete recover of the total value needed to implement the transmission grid, in addition an economic signal supposedly to support the expansion planning of new plants and loads. However, the results obtained by the nodal mathematical model are not always consistent with the basic assumptions of a cost allocation methodology. Thus, this work presents an analysis of the Nodal methodology, used in Brazil, providing in detail the mathematical modeling behind the method along with its main advantages and disadvantages, aiming to observe the behavior of the value from the tariff and the influence of the electrical parameters used in its calculation. For this purpose, a study case is presented and validated in the official program, used by ANEEL, to calculate the tariff, the Nodal, and from this case modification are made in the electrical parameters used by the software, such as impedance, capacity, load and generation. In this sense, the paper seeks to contribute to this analysis by investigating in a quantitative way, what variations occur in the tariff values, by different simulation scenarios. The TUST values, both for load and generation, are presented and their behavior discussed aiming for a greater transparency of the current method.